2021
DOI: 10.21203/rs.3.rs-442908/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical Model of SMD of Hydrodynamic Ultrasonic Atomizing Nozzle Based on Orthogonal Design

Abstract: The hydrodynamic ultrasonic atomization nozzle has excellent atomization performance and has a wide range of applications in the field of spray dust reduction. A mathematical model the SMD of the nozzle was established to evaluate the SMD of such nozzles using the custom-designed spraying experiment platform and orthogonal design methods. The interaction between the SMD of the nozzle and the three influencing factors, i.e., air pressure, water pressure and outlet diameter were obtained. Through range analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…et al (2021). Wu G.G. et al, (2021), pointed out that the latter has excellent atomisation performance, Park J. et al, (2022), showed that wind field can affect the deposition coverage of droplets, Tian Z. et al, (2022), showed that the presence of a wind field can increase the penetration of droplets between the blades, Liu C. et al, (2023), showed that a conical wind field can increase the deposition coverage of droplets, and Butler M.C.…”
Section: Introductionmentioning
confidence: 99%
“…et al (2021). Wu G.G. et al, (2021), pointed out that the latter has excellent atomisation performance, Park J. et al, (2022), showed that wind field can affect the deposition coverage of droplets, Tian Z. et al, (2022), showed that the presence of a wind field can increase the penetration of droplets between the blades, Liu C. et al, (2023), showed that a conical wind field can increase the deposition coverage of droplets, and Butler M.C.…”
Section: Introductionmentioning
confidence: 99%